Paediatric neurodisability and sleep disorders: clinical pathways and management strategies - Aoife McDonald; Desaline Joseph (BMJ Publishing Group, 2019)
Sleep disorders are common in children with neurodisability. Their presentation is often complex. This complexity of presentation can make sleep disorders in children with neurodisability daunting to diagnose and manage. Both parents and healthcare professionals have identified sleep disorders as a healthcare outcome that they prioritise in children with neurodisability. We aim to explore the challenges of diagnosing sleep problems, discuss common difficulties with sleep in children with neurodisability and will touch on how to set up a service to support and manage sleep, working through case examples.